Winter Tick Burdens for Moose Are Positively Associated With Warmer Summers and Higher Predation Rates - Hoy, Sarah R.; Vucetich, Leah M.; Peterson, Rolf O.; Vucetich, John A. (Frontiers in Ecology and Evolution, 2021)
Climate change is expected to modify host-parasite interactions which is concerning because parasites are involved in most food-web links, and parasites have important influences on the structure, productivity and stability of communities and ecosystems. However, the impact of climate change on host–parasite interactions and any cascading effects on other ecosystem processes has received relatively little empirical attention. We assessed host-parasite dynamics for moose (Alces alces) and winter ticks (Dermacentor albipictus) in Isle Royale National Park over a 19-year period. Specifically, we monitored annual tick burdens for moose (estimated from hair loss) and assessed how it covaried with several aspects of seasonal climate, and non-climatic factors, such as moose density, predation on hosts by wolves (Canis lupus) and wolf abundance. Summer temperatures explained half the interannual variance in tick burden with tick burden being greater following hotter summers, presumably because warmer temperatures accelerate the development of tick eggs and increase egg survival. That finding is consistent with the general expectation that warmer temperatures may promote higher parasite burdens. However, summer temperatures are warming less rapidly than other seasons across most regions of North America. Therefore, tick burdens seem to be primarily associated with an aspect of climate that is currently exhibiting a lower rate of change. Tick burdens were also positively correlated with predation rate, which could be due to moose exhibiting risk-sensitive habitat selection (in years when predation risk is high) in such a manner as to increases the encounter rate with questing tick larvae in autumn. However, that positive correlation could also arise if high parasite burdens make moose more vulnerable to predators or because of some other density-dependent process (given that predation rate and moose density are highly correlated). Overall, these results provide valuable insights about interrelationships among climate, parasites, host/prey, and predators.